Rancang Bangun Company Profile Berbasis Web Menggunakan Metode Waterfall (Studi Kasus : APM Frozen Food) - Bias Yulisa Geni; Asep Supriyadi; Husnul Khotimah; Weni Indri Yanti (Program Studi Teknik Informatika Universitas Nusa Putra, 2024)
This research explores the development of a company profile website with a holistic approach using Bootstrap, CodeIgniter 3, Apache, and MySQL as the technological foundation. The main focus is to optimally integrate the frontend and backend. The research methodology includes in-depth analysis of requirements, responsive design, implementation with CodeIgniter 3 for backend logic, utilization of Apache as a server, and MySQL for efficient database management. Active observations, interviews, and thorough documentation resulted in concrete solutions for this project. The results include not only successful implementation of the latest technology but also strengthened website performance and responsibility. This research has a positive impact by increasing the effectiveness of company website development and creating an integrated and optimally responsive environment for user needs.